(untitled) (Environmental Smoke, 2023)
Growth efforts and the growing population have been creating an adverse impact on our bio-diversity therefore human health is at higher risk, and human civilization came closer to a severe Environmental crisis. Impacts of environmental degradation especially of air and water pollution have been severe and challenging in Bangladesh, and generally, city dwellers face higher pollution levels than rural residents in their everyday lives. The broad aim of this study is to assess the environmental awareness level of the population of Dhaka city. Based on both primary and secondary data, the study reveals a huge lack of awareness of environmental challenges and the necessity of handling these concerns with appropriate initiatives. Gender perspective reveals women’s potential areas of contribution to handling environmental challenges. Both men and women need to be brought under strategic environmental awareness and education programs for sustainable and healthy urban life in Bangladesh, the study concludes.